Un percorso di ricerca in mostra - Biagioli, Beatrice (Annali di Storia di Firenze, 2017)
Here is presented the journey of the exhibition Correct and prevent. The reform policy of Pietro Leopoldo and Correction House in Fortezza da Basso in Florence, held at the State Archive of Florence and open to the public from the 22nd to the 27th of February 2016, with an exhibition of hand-written testimonies extracted from the funds of various courts, maps, paintings and printed materials. The contribution gives an overview of the whole, focusing particularly on significant documents that bring out the interpretations and insights of the issues in question.